2010
DOI: 10.1007/s10354-010-0742-0
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen akuter Höhenexposition: Welche Höhe ist gesundheitlich verträglich?

Abstract: Exposures to natural and simulated altitudes are combined with a reduction of the available oxygen (hypoxia) and may provoke health problems or even emergencies. Although millions of people are living at high altitudes, are regularly or occasionally performing mountain sport activities, are transported by airplanes, and are increasingly frequently exposed to hypoxia at their workplace, e.g. with fire control systems, there is no consensus about the level of hypoxia which is well tolerated by most of human bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Controlled hypoxia is known for its low risks and potential short and long-term benefits on physiological parameters (e. g., increased erythropoiesis, angiogenesis, antioxidant capacity, improved exercise performance) [24][25][26]46,47]. A recent review suggested that controlled hypoxia increases BDNF levels in the brain as well as in the blood of rodents [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled hypoxia is known for its low risks and potential short and long-term benefits on physiological parameters (e. g., increased erythropoiesis, angiogenesis, antioxidant capacity, improved exercise performance) [24][25][26]46,47]. A recent review suggested that controlled hypoxia increases BDNF levels in the brain as well as in the blood of rodents [48].…”
Section: Discussionmentioning
confidence: 99%
“…In general the benefits and detriments of hypoxia are determined by the severity, frequency and duration of hypoxia exposures [24]. However, in the case of controlled hypoxia, e. g., in the context of altitude training, the reduction in the oxygen supply to the organism is mostly harmless [25]. An insufficient supply of O2 leads to a decrease in the O2 saturation of the blood (hypoxemia).…”
Section: Introductionmentioning
confidence: 99%
“…An important clinical problem posed by this research is whether iron deficiency may increase susceptibility to AMS or other high-altitude diseases. Although some treatments have been shown to effectively reduce the incidence and severity of AMS, gradually ascending to high altitudes seems to be the best strategy for the prevention of altitude sickness [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that some drugs may prevent AMS, but these prophylactic interventions may be accompanied with serious adverse effects [ 6 ]. Recently, clinical trials with healthy volunteers suggested that intravenous iron supplementation may protect against AMS.…”
Section: Introductionmentioning
confidence: 99%